Sol-Gel Syntheses of Zinc Oxide and Hydrogenated Zinc Oxide (ZnO:H) Phases - Joshua Lelesi Konne; Bright Obum Christopher (Journal of Nanotechnology)
ZnO synthesized by chemical precipitation with varying starch concentrations (0.00, 0.01, 0.02, 0.05, 0.10, 0.15, and 0.20%) as stabilizing agent was used in making ZnO:H when placed in a glass tube under mild heat and hydrogen (H2) gas flow for 2 mins. Observations showed that the sample colour changed from white to light brown and finally to dark brown during the process particularly for the ZnO-starch samples. XRD data of ZnO (0.02%) and ZnO:H (0.02%) showed ZnO as the major phase with Zn(OH)2 impurity phase and a new ZnO:H peak at 2θ, 29.60° for ZnO and ZnO:H, respectively. The estimated particle sizes determined from XRD were 47 and 30 nm, respectively. The SEM of the 0.02% ZnO appeared more microporous and needle-like than those of 0.01%, while the EDX of both confirmed Zn and O as the main components. Different conductivities of 30.90 and 27.50 μS/cm were obtained for ZnO and ZnO:H samples in ethanol, respectively. Also, the UV-Vis absorption for both showed n-type and p-type material absorption bands at 310 cm−1, while the intensities of all the characteristic ZnO IR bands at 430–552 (ZnO vibrations) and 1500–1640 cm−1 (Zn-O stretching) increased for the corresponding ZnO:H samples.